2018
DOI: 10.1038/s41467-017-02436-w
|View full text |Cite
|
Sign up to set email alerts
|

Self-generated surface magnetic fields inhibit laser-driven sheath acceleration of high-energy protons

Abstract: High-intensity lasers interacting with solid foils produce copious numbers of relativistic electrons, which in turn create strong sheath electric fields around the target. The proton beams accelerated in such fields have remarkable properties, enabling ultrafast radiography of plasma phenomena or isochoric heating of dense materials. In view of longer-term multidisciplinary purposes (e.g., spallation neutron sources or cancer therapy), the current challenge is to achieve proton energies well in excess of 100 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 60 publications
2
34
0
Order By: Relevance
“…Such surface quasi-static fields have already been reported in multiple studies of the interaction of intense lasers with dense plasmas (see e.g. [59][60][61][62]), and can be induced by a variety of physical processes (see e.g. [63][64][65][66]).…”
Section: Long-gradient Regimementioning
confidence: 92%
“…Such surface quasi-static fields have already been reported in multiple studies of the interaction of intense lasers with dense plasmas (see e.g. [59][60][61][62]), and can be induced by a variety of physical processes (see e.g. [63][64][65][66]).…”
Section: Long-gradient Regimementioning
confidence: 92%
“…In addition, the presence of a low density preformed plasma on the rear surface of the target in advance of the peak of the laser pulse has been shown to enhance Weibel-like instability formation that can lead to strong modulations in the accelerated proton beam [45,46]. Even without filamentation, recent work by Nakatsutsumi et al using higher intensities and thinner targets demonstrated that strong azimuthal magnetic fields on the rear surface can inhibit proton acceleration and impact the beam quality [47]. With these simulations, we investigate the influence of pulse duration on emittance growth mechanisms.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…However if l s ?λ D , the field is reduced to = E k T el B e s [34]. Alternatively, strong magnetic fields can inhibit sheath formation by confining or scattering hot electrons away from the central axis [47]. In figure 8, the maximum proton energies observed in the experiment are compared with predictions based on the analytical model described by Schreiber et al [50].…”
Section: Discussionmentioning
confidence: 98%
“…The parameter space of focused intensity and pulse duration for the experiments using EPMs and tightly focused OAP (only for I > 10 21 W=cm 2 ). Squares represent EPM experiments that have been done [126,127], and circles represent the parameters of tightly focused OAP. The value for the Texas PW stems from an approximate estimate based on typical laser parameters in conjunction with a f/#1 OAP.…”
Section: Plasma-based Tight Focusingmentioning
confidence: 99%